If you give a mouse a cookie - Numeroff, Laura Joffe; Bond, Felicia (New York Laura Geringer Books, 2010)
Relating the cycle of requests a mouse is likely to make after you give him a cookie takes the reader through a young child's day
Sequel: If you give a moose a muffin
2
Keywords: Mice -- Fiction